Pengaruh Isu Overtourism Terhadap Sustainable Tourism Yang Ada di Bali - Ni Putu Wisna Nadya Baby Bellinda; Putu Sri Arta Jaya Kusuma (Fakultas Ekonomi Program Studi Akuntansi Universitas 45 Surabaya, 2024)
Abstract The global economy has suffered as a result of the COVID-19 health crisis, particularly the travel and tourism industry. The COVID-19 pandemic has caused major losses for the tourism industry. However, as the impact of COVID-19 decreases, current tourism behavior causes the possibility of overtourism. Over the past few years, the desire for “revenge tourism” has increased as a result of negative feelings caused by the COVID-19 pandemic. Excessive tourism also has a negative social impact from a psychological point of view, but from a psychological point of view, it may be due to negative emotions accumulated over a period of time. Bali is also facing poor sustainable tourism development after the drastic economic decline caused by the COVID-19 pandemic. With the excessive increase in the number of tourists, will this have a negative impact on sustainable tourism development in Bali? This research was created to find out whether the overtourism that is being rumored will have an impact on workers for tourism development in Bali after the COVID-19 pandemic occurred several years ago.